Molecular Detection and Diagnosis of Phytoplasma Infection in Cassava (Manihot esculenta Crantz) in Eastern Visayas, Philippines - Erlinda A, Vasquez,; Lucia M, Borines,; Fatima G, Palermo, Lady (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Phytoplasma disease is a threat to the cassava industry but little is known aboutthe disease in the country. This study was conducted to develop and optimize a protocolfor the detection of phytoplasma and determine the existence of phytoplasma strains inthe different cassava growing areas in Eastern Visayas, Philippines.PCR reaction using primer pair PA2F/R and nested primer pair NPA2F/R aswell as the use of primer pair P1/P7 followed by nested primer pair R16F2n/R2 withslight modifications in the thermocycling conditions detected phytoplasma infectingcassava.Ten out of the eleven areas in Eastern Visayas, a scale insect and a cassavagrown from tissue culture tested positive for phytoplasma using nested primer pairsNPA2F/R and R16F2n/R16R2. Six band patterns were detected when NPA2F/R primeramplicons were digested with RsaI and MspI restriction enzymes suggesting that morethan one strain of phytoplasma infect cassava.